2023
DOI: 10.1186/s11658-023-00441-0
|View full text |Cite
|
Sign up to set email alerts
|

Can precancerous stem cells be risk markers for malignant transformation in the oral mucosa?

Abstract: Accurate assessment of the carcinogenic potential of oral mucosal diseases can significantly reduce the prevalence of oral cancer. We speculate that precancerous stem cells (pCSCs) arise during the evolution of carcinomas based on long-term experimental findings, published literature, and the cancer stem cell (CSC) theory, wherein pCSCs exist in precancerous lesions and have characteristics of both CSCs and normal stem cells. This apparently contradictory feature may be the foundation of the reversible transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…Chromosomal instability (CIN) is an important trait of tumor cells and is characterized by abnormal numbers and structures. CIN is commonly found in a variety of solid tumors and malignant hematological diseases [ 5 , 6 ]. Studies have shown that specific marker chromosomes have become pivotal targets for the diagnosis, treatment and prognostic prediction of chronic myeloid leukemia and other tumors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal instability (CIN) is an important trait of tumor cells and is characterized by abnormal numbers and structures. CIN is commonly found in a variety of solid tumors and malignant hematological diseases [ 5 , 6 ]. Studies have shown that specific marker chromosomes have become pivotal targets for the diagnosis, treatment and prognostic prediction of chronic myeloid leukemia and other tumors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%